2015
DOI: 10.1101/018770
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The complex admixture history and recent southern origins of Siberian populations

Abstract: Although Siberia was inhabited by modern humans at an early stage, there is still debate over whether this area remained habitable during the extremely cold period of the Last Glacial Maximum or whether it was subsequently repopulated by peoples with a recent shared ancestry. Previous studies of the genetic history of Siberian populations were hampered by the extensive admixture that appears to have taken place among these populations, since commonly used methods assume a tree-like population history and at mo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 95 publications
(131 reference statements)
6
30
0
1
Order By: Relevance
“…This procedure helps to avoid the potential effect of high relatedness among individuals in isolated populations from Siberia, as well as uneven sample sizes. Our PCA analysis to some extent recaps previously reported patterns of genetic structure across Eurasia (Pugach et al, ; Wong et al, ). PC1 corresponds to west‐east differentiation, while the second PC generally differentiates northern and southern populations.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…This procedure helps to avoid the potential effect of high relatedness among individuals in isolated populations from Siberia, as well as uneven sample sizes. Our PCA analysis to some extent recaps previously reported patterns of genetic structure across Eurasia (Pugach et al, ; Wong et al, ). PC1 corresponds to west‐east differentiation, while the second PC generally differentiates northern and southern populations.…”
Section: Resultssupporting
confidence: 86%
“…In agreement with ROH analysis, the majority of Siberian populations also reveal an increased number of within‐population shared IBD segments with high correlation coefficient between IBD sharing and Ne . Similar to previous studies (Pugach et al, ; Yunusbayev et al, ), Nganasans demonstrates unusually high IBD sharing with other Siberian populations. The fact that a majority of modern Siberian people share excessive IBD sharing (and possibly the same set of ancestors) seems to contradict long‐term isolation and very high genetic differentiation observed within Siberia.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Adding rivers to the regression model resulted in an increase in the amount of variation explained by the model (Table ), with rivers being a significant predictor ( p ‐value = 0.01). We then jack‐knifed over populations (Pugach et al ; Ramachandran et al, ) and identified three populations as outliers—Sikuani, Siona, and Nukak—groups that appeared as outliers in the MDS plot as well (Figure ). We performed the multiple regression analysis excluding the outliers, and this resulted in an increase of 3.4% in the R square value, a better correlation between genetic and geographic distances, and geography becoming a significant predictor factor ( p ‐value < 0.05) (Table and Supporting Information Figure S8), although rivers were no longer a significant predictor of genetic subdivision.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a multiple regression analysis on distance matrices (MRM) (Goslee and Urban, ) with the form: MRM(as.dist(gen.dist) – as.dist(geo.dist) + as.dist(rivers.dist)) was performed. This analysis takes into consideration a matrix of geographic distances and a matrix of proximity along rivers as predictor variables of the genetic distances (pairwise Φ ST values) between populations (Pugach et al, ; Yunusbayev et al, ). For the matrix of river distances, a value of zero was given to populations living along the same river or on rivers that are closely connected, and a value of one was given to populations living on different rivers.…”
Section: Methodsmentioning
confidence: 99%